Reviewing the links between violent extremism and personality, personality disorders, and psychopathy. Issue 3 (4th May 2021) - Corner, Emily; Taylor, Helen; Van Der Vegt, Isabelle; Salman, Nadine; Rottweiler, Bettina; Hetzel, Florian; Clemmow, Caitlin; Schulten, Norah; Gill, Paul
ABSTRACT: Many early published analyses of the terrorist placed psychopathy as the core explanatory variable for terrorist behaviour. This speculative opinion was derived mainly from popular culture, and the desire to attribute mental disorders to those committing such violent acts. Poor research designs and a lack of empiricism ultimately undermined these arguments in favour of terrorism being rooted in disorders of personality. Multiple studies supporting psychopathic and personality-level explanations were conducted in the absence of rigorous clinical diagnostic procedures. Despite the methodological issues, concluding remarks from this research continues to hold instinctive appeal across the research field. This incentivises a need for a rigorous synthesis of the evidence base. The objective of this systematic review is to assess the impact of personality upon attitudes, intentions, and behaviours in the context of radicalisation and terrorism. This paper follows the same systematic process as the Gill et al. paper in this special issue. However, we use the model to interrogate the existing empirical literature on personality and terrorism in terms of its coverage, common themes, methodological strengths and weaknesses and implications. The search strategy for the systematic review is based on the Campbell Collaboration method. Results and their implications are discussed.